2004
DOI: 10.1074/jbc.m312356200
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of Third-generation Cephalosporins by Class C β-Lactamases

Abstract: Bacterial resistance to the third-generation cephalosporins is an issue of great concern in current antibiotic therapeutics. An important source of this resistance is from production of extended-spectrum (ES) ␤-lactamases by bacteria. The Enterobacter cloacae GC1 enzyme is an example of a class C ES ␤-lactamase. Unlike wild-type (WT) forms, such as the E. cloacae P99 and Citrobacter freundii enzymes, the ES GC1 ␤-lactamase is able to rapidly hydrolyze third-generation cephalosporins such as cefotaxime and ceft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…Among the enzymes whose kinetic properties have been studied, the AmpC ␤-lactamase from Enterobacter cloacae P99 is the most similar to Mox-1 in amino acid sequence with 45% identity, and the RMSD is 3.03 Å. The RMSD value between Mox-1 and an extended-spectrum enzyme (GC1) from E. cloacae (45% identical in primary sequence) was 3.29 Å. GC1 is 98% identical to P99, and it was reported that GC1 acquired its extended substrate specificity by the insertion of 3 amino acids in the ⍀ loop (22). The large RMSD suggests that the extended-spectrum ␤-lactamase activity is different between Mox-1 and GC1.…”
Section: Resultsmentioning
confidence: 82%
“…Among the enzymes whose kinetic properties have been studied, the AmpC ␤-lactamase from Enterobacter cloacae P99 is the most similar to Mox-1 in amino acid sequence with 45% identity, and the RMSD is 3.03 Å. The RMSD value between Mox-1 and an extended-spectrum enzyme (GC1) from E. cloacae (45% identical in primary sequence) was 3.29 Å. GC1 is 98% identical to P99, and it was reported that GC1 acquired its extended substrate specificity by the insertion of 3 amino acids in the ⍀ loop (22). The large RMSD suggests that the extended-spectrum ␤-lactamase activity is different between Mox-1 and GC1.…”
Section: Resultsmentioning
confidence: 82%
“…Given the conservation of the avibactam binding pocket residues and the importance of these residues in ␤-lactam recognition and catalysis (25)(26)(27)(28)(29), we investigated whether any variations in these might compromise the inhibition potency of avibactam while still allowing hydrolysis of the ␤-lactam drug and thus result in resistance. Spontaneous resistance frequency experiments were carried out in several isolates carrying class C ␤-lactamases, with an initial focus on Enterobacteriaceae spp.…”
Section: Resultsmentioning
confidence: 99%
“…However, as seen in X-ray crystallographic analysis structures of class C b-lactamase, [48][49][50][51][52][53] there is no acidic amino acid residue corresponding to Glu166 in class A in the active site, while a residue corresponding to Lys73 in class A is seen (Lys67). In place of Glu166 in class A, a tyrosine residue (Tyr150) exists in the active site of class C. Some studies 8,48,54) have suggested that the side chain of Tyr150 is in a deprotonated state due to the special surrounding environment of class C and plays a role as a general base.…”
Section: Deacylation Mechanism Of Class C B-lacta-masementioning
confidence: 99%